Orientalist Approaches to the Qur’an: Epistemological Motives and Frameworks - Nuruddin Zaini; Abdullah Safei (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
This study analyzes the principal motives underlying orientalist scholarship on the Qur’an along with the arguments advanced by orientalist scholars. Such an inquiry is considered significant given that orientalist studies of the Qur’an have developed in a massive, systematic, and influential manner within global academic discourse. The research employs a qualitative method in the form of descriptive-analytical library research, supported by a sociological approach to examine the relationship between knowledge and power in the production of orientalist discourse. Data are collected through documentation of relevant orientalist works, while data analysis is conducted using content analysis. The findings indicate that, at a fundamental level, orientalist approaches to the Qur’an are driven by three main tendencies: (1) a motive to delegitimize the authority of the Qur’an, (2) a motive to denigrate the Prophet Muhammad (peace be upon him), and (3) the assumption that the Qur’an is a product of Jewish–Christian textual influence. One key argument frequently advanced is the claim that the Qur’an is closely connected to pre-Islamic religious traditions and texts. Within the framework of Jewish and Christian epistemic hegemony, orientalist scholars tend to employ their own scriptures as normative parameters in evaluating the Qur’an, particularly through comparative methods that emphasize the identification of textual similarities as the basis for their conclusions.